The Performance of Individual Service Providers (PJLP) in Archival Management in the Province of DKI Jakarta - Ari Imansyah; Muh. Ilham; Ella Wargadinata (Sean Institute, 2025)
This study aims to analyze the effectiveness of the performance of Individual Other Service Providers (PJLP) in managing archives within the DKI Jakarta Provincial Government, focusing on five main agencies, namely the Library and Archives Service (Dispusip), Regional Asset Management Agency (BPAD), Regional Personnel Agency (BKD), Regional Financial Management Agency (BPKD), and the Public Works, Spatial Planning, and Land Agency (DCKTRP). The study uses a descriptive qualitative approach, with data collection techniques through in-depth interviews with structural officials and PJLP, as well as documentation studies. The theoretical framework used is the performance theory from Kasmir (2018) which includes six work criteria: quality, quantity, timeliness, cost efficiency, supervision, and work relationships. In addition, this study also uses a government science approach through the principle of good governance and the Kybernology theory from Taliziduhu Ndraha to understand the position of PJLP in the regional government bureaucracy system. The results of the study show that the performance of PJLP is considered quite effective in supporting archive management, especially in terms of quality and cost efficiency. Agencies such as Dispusip and BPKD noted the performance of PJLP which had minimal errors, was disciplined, and complied with SOPs. Work productivity was also high, with a clear daily workload and measurable reporting. In terms of cost efficiency, all agencies stated that the existence of PJLP was more efficient and safer than outsourcing. However, there are still significant challenges that affect overall effectiveness, such as the educational background of PJLP which is not yet appropriate, the annual contract status that does not guarantee sustainability, limited work facilities, the lack of ASN archivists as supervisors, and the absence of uniform standard operating procedures between agencies.